Clarification, Prioritization, and Examination of the Role of Financial Corruption Dimensions in Financial Statement Manipulation - Hasan Zalaghi; Kaveh Ghaderi; Abbas Aflatooni (بررسی‌های حسابداری و حسابرسی)
ObjectiveThe higher the level of corruption in a society, the greater the number of justifications for immoral actions and behaviors. Therefore, companies that operate in highly corrupted environments face a weaker financial reporting system. The current research aims to explain various types of financial corruption and investigate their relationship with financial misstatements. Based on the theoretical foundations, three dimensions of administrative-operational corruption, administrative corruption, and political corruption were identified, and their components and indicators were explained.MethodsThe research employed a survey method with a cross-sectional design. The statistical population of the research included faculty members, financial managers, and members of the public accountant community. The sample size comprised 193 individuals, and the data were collected using a researcher-designed questionnaire. To check the validity of the questionnaire, content validity was used and to measure its reliability, Cronbach's alpha method was used. SPSS and AMOS software were used to test the hypotheses.ResultsThe results indicated a direct and significant relationship between the commercial and political aspects of corruption and financial misstatements. However, no significant relationship was found between the administrative-operational dimension and the financial misstatements. Moreover, the results of the regression analysis indicated the presence of positive and significant relationships between the dimensions of commercial and political corruption indicators and financial misstatements. In addition, the results of Structural Equation Modeling showed the acceptability of the collected data and the fit of the conceptual model of the research.ConclusionIt can be argued that corruption in hiring employees and managers alone is not a sufficient factor for the occurrence of corruption and, consequently, distortion in financial statements. However, corruption in the employment of managers and employees can lead to distortions in financial statements through embezzlement, receiving bribes, extortion, influencing company tenders, fraud by managers, and conflict of interests. Also, the results showed that connection with political parties and dependence on the government, connection with special customers and not dealing with new customers and ethnocentrism can lead to distortion in financial statements. This type of communication not only affects the financial resources of the companies but also motivates the managers to provide reports and financial statements under the opinions of the government. Furthermore, on one hand, bribery through management collusion with other people can lead to the concealment of facts and provide misleading financial statements by lengthening and complicating financial reports. In addition, management can distort financial statements through manipulation of financial reports and fraud for personal gain. On the other hand, purchasing goods, materials, and services needed by the company's employees from institutions or companies in which they or their relatives have interests can increase the cost of goods and services, thereby reducing profits. Embezzlement also leads to illegal changes in the company's assets and liabilities. These changes can have serious effects on the accuracy and reliability of financial reporting. Moreover, extortion by employees can lead to the removal of customers and suppliers of raw materials of the company, hence the financial statements are also subject to change. Based on the results of the structural equation model, the indicators used to measure the existing variables have appropriate factor loadings and can be used to measure the variables of administrative corruption, commercial corruption, political corruption, and distortion in financial statements. Also, the results indicate the impact of financial statements on commercial corruption and political corruption.